The Impact of Price Perception and Service Quality on Consumer Purchase Interest in Biznet Home Internet Services in Kediri - Marcela, Tiara Putri; Zawawi, Zawawi (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
This research endeavor focuses on to examine the impact of Price Perceptions and Service Quality on Purchase Interest for Biznet Home Internet services in Kediri City. The research targets Biznet Home wifi users in the area, with a sample of 104 respondents selected based on Ghozali's formula. Data were gathered through Google Forms and analyzed using Partial Least Squares (PLS) techniques. The analysis shows that in terms of Price Perception, the most significant factor is the wide variation in prices offered for Biznet Home Internet services according to the quality provided (X1.2). Meanwhile, in the Service Quality variable, the most prominent factor is the responsiveness of Biznet Home Internet officers in handling service problems faced by consumers (X2.2). These findings highlight the key elements in Price Perception and Service Quality that most significantly influence customer purchase interest.